Magnetic Nanoparticles Attached to the NK Cell Surface for Tumor Targeting in Adoptive Transfer Therapies Does Not Affect Cellular Effector Functions - Sanz-Ortega, Laura; Rojas, José M.; Portilla, Yadileiny; Pérez-Yagüe, Sonia; Barber, Domingo F. (Frontiers in Immunology, 2019)
Adoptive cell transfer therapy is currently one of the most promising approaches for cancer treatment. This therapy has some limitations, however, such as the dispersion of in vivo-administered cells, causing only a small proportion to reach the tumour. Nanotechnological approaches could offer a solution for this drawback, as they can increase cell retention and accumulation in a region of interest. In particular, strategies employing magnetic nanoparticles (MNPs) to improve targeting of adoptively transferred T or NK cells have been explored in mice. In vivo magnetic retention is reported using the human NK cell line NK-92MI transfected with MNPs. Primary NK cells are nonetheless highly resistant to transfection, and thus we explore in here the possibility of attaching the MNPs to the NK cell surface to overcome this issue, and examine whether this association would affect NK effector functions. We assessed the attachment of MNPs coated with different polymers to the NK cell surface, and found that APS-MNP attached more efficiently to the NK-92MI cell surface. In association with MNPs, these cells preserved their main functions, exhibiting a continued capacity to degranulate, conjugate with and lyse target cells, produce IFN-γ, and respond to chemotactic signals. MNP-loaded NK-92MI cells were also retained in an in vitro capillary flow system by applying an EMF. A similar analysis was carried out in primary NK cells, isolated from mice, and expanded in vitro. These primary murine NK cells also maintained their functionality intact after MNP treatment and were successfully retained in vitro. This work therefore provides further support for using MNPs in combination with EMFs to favour specific retention of functional NK cells in a region of interest, which may prove beneficial to adoptive cell-therapy protocols.